Green brand Sebagai Mediasi Kualitas Produk dan Strategi Marketing terhadap Loyalitas Konsumen Produk The body shop di Denpasar - Ni Putu Angelina Septiari; Ida Bagus Gede Agung Yoga Pramana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
In an era marked by heightened environmental awareness, consumers increasingly prefer products that offer sustainable value. As a brand recognized for its environmentally conscious practices, The body shop needs to understand the role of green brand perception in shaping customer loyalty. Beyond the importance of product quality and marketing strategy, green brand is presumed to mediate the influence of these factors on consumer loyalty. This study aims to examine the effects of product quality and marketing strategy on customer loyalty toward The body shop in Denpasar, with green brand serving as a mediating variable. Using non-probability sampling with a purposive sampling approach, this quantitative research collected data through questionnaires distributed to 150 customers of The body shop in Denpasar. The data were analyzed using Structural Equation Modeling (SEM) to assess the relationships among variables. The findings reveal that product quality has a significant positive effect on customer loyalty, whereas the direct effect of marketing strategy is not significant. Green brand, however, shows a significant influence on loyalty. Mediation testing further indicates that green brand strengthens the effects of both product quality and marketing strategy on consumer loyalty. These results highlight the central role of green brand as a key mediator in the formation of loyalty toward The body shop in Denpasar. Consequently, the company is encouraged to continue emphasizing environmentally responsible values within its brand image to enhance and sustain customer loyalty.